2022
DOI: 10.1186/s40478-022-01449-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gulf war toxic exposures after mild traumatic brain injury

Abstract: Chemical and pharmaceutical exposures have been associated with the development of Gulf War Illness (GWI), but how these factors interact with the pathophysiology of traumatic brain injury (TBI) remains an area of study that has received little attention thus far. We studied the effects of pyridostigmine bromide (an anti-nerve agent) and permethrin (a pesticide) exposure in a mouse model of repetitive mild TBI (r-mTBI), with 5 impacts over a 9-day period, followed by Gulf War (GW) toxicant exposure for 10 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 69 publications
2
3
0
Order By: Relevance
“…The hypothesis that emerged from early studies was that GWI might be a disorder that is also expressed neuropathologically. More recently, animal studies have indicated that the effects of toxicant exposure in combination with TBI can lead to more severe consequences in the brain [36]. Both our behavioral and immunohistochemistry results support the additive effect of the combined insults.…”
Section: Discussionsupporting
confidence: 81%
“…The hypothesis that emerged from early studies was that GWI might be a disorder that is also expressed neuropathologically. More recently, animal studies have indicated that the effects of toxicant exposure in combination with TBI can lead to more severe consequences in the brain [36]. Both our behavioral and immunohistochemistry results support the additive effect of the combined insults.…”
Section: Discussionsupporting
confidence: 81%
“…The finding from a previous study that severe GWI was more frequent in veterans who were GWI+/PTSD+ compared to veterans who were GWI+/PTSD-is consistent with this line of thinking (Malhotra et al, 2023). This account of GWI is similar to a recent theory of GWI that posits that the condition, especially its more severe manifestation, is the result of "multiple hits" of neurotoxicant exposures and traumatic brain injury (Ferguson et al, 2022) and the reason many murine models of GWI combine stress and neurotoxicant exposures to recapitulate GWI (Ashbrook et al, 2018;Macht et al, 2019;Michalovicz et al, 2020).…”
Section: Discussionsupporting
confidence: 80%
“…Hence, our measurements in patient samples are highly relevant, as the findings can be directly translated to clinical settings. Individuals who have endured mTBI, and particularly those with rmTBI, often have concomitant long-term neurological symptoms, including a decline in cognition, motor abilities and changes in behavior [81][82][83][84][85]. Extensive neuropsychological testing procedures have been established to evaluate the long-term effects, which include clinical assessments, as well as self-administered questionnaires, such as NSI-22 and PHQ-9 [86][87][88].…”
Section: Discussionmentioning
confidence: 99%